Environmental economics : concepts, methods and policies - Thampapillai, Dodo J.; Ruth, Matthias (Abingdon, Oxon ; New York, NY : Routledge, 2019)
Environmental Economics explores the ways in which economic theory and its applications, as practised and taught today, must be modified to explicitly accommodate the goal of sustainability and the vital role played by environmental capital. Pivoting around the first and second laws of thermodynamics, as well as the principles of ecological resilience, this book is divided into five key parts, which includes extensive coverage of environmental microeconomics and macroeconomics. It drills down into issues and challenges including consumer demand; production and supply; market organisation; renewable and non-renewable resources; environmental valuation; macroeconomic stabilisation, and international trade and globalisation. Drawing on case studies from forestry, water, soil, air quality, and mining, this book will equip readers with skills that enable the analyses of environmental and economic policy issues with a specific focus on the sustainability of the economy. Rich in pedagogical features, including key concepts boxes and review questions at the end of each chapter, this book will be a vital resource for upperlevel undergraduate and postgraduate students studying not only environmental economics/ecological economics but also economics in general.
PART III Macroeconomics and the environment10 Some important concepts in macroeconomics; 11 Environmental capital: investment and depreciation; 12 Environmental macroeconomics: short-run analysis I; 13 Environmental macroeconomics: short-run analysis II; 14 Environmental macroeconomics: long-run analysis; 15 International trade and globalisation; PART IV Valuation; 16 Valuation of environmental capital: microeconomic basis; 17 Valuation of environmental capital: macroeconomic basis -- I; 18 Valuation of environmental capital: macroeconomic basis -- II; PART V Policy; 19 Environmental policies
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Environmental economics; Economic development -- Environmental aspects; BUSINESS & ECONOMICS / Development / Sustainable Development; NATURE / Ecology; POLITICAL SCIENCE / Public Policy / Environmental Policy